Eksplorasi Budaya Etnomatika dengan Susu Ladok Khas Trenggalek Diimplementasikan pada Materi Pengolahan Data di Kelas IV SDN 1 Ngantru - Wiryanto Wiryanto; Ika Rahmawati; Nurhayati Mawaddah (Journal Innovation In Education, 2024)
As an effort to introduce local culture associated with teaching materials, the teacher made a learning strategy that discussed the exploration of ethnomatic culture with Trenggalek Ladok typical milk which was implemented in data processing materials in grade IV SDN 1 Ngantru. The purpose of this study is to increase students' understanding of local culture through the local culture of ladok milk applied in data processing materials. In this study using the class action method. With research instruments used are observation, interviews, and documentation. The results showed that the implementation of ethnomatic cultural exploration with Ladok milk in data processing material in grade IV SDN 1 Ngantru can increase students' understanding of local culture. This is evidenced by the increase in student learning outcomes and student enthusiasm in participating in learning.